Revealing Gender Inequality in Selection of Topics for Comments on Infidelity in Gossip Channel - Dewinda, Viona Musti; Hamzah, Hamzah (English Language and Literature, 2024)
This research aimed to employ Van Dijk's Ideological Square to examine gender inequality in infidelity news comments on YouTube. The study used a qualitative research technique. According to the results, the most popular netizen comments concerned for Virgound and Syahnaz were "bad personality," with 53 (23%) and 59 (26%), respectively. This category shows that both commonly used unfavorable personal qualities as the major basis for their discourse topics. The researcher discussed several concerns online users raised regarding Virgoun and Syahnaz. There was a noticeable gender inequality in the YouTube comments on the Virgoun and Syahnaz episode. Despite these parallels, men and women were viewed differently by society, with men generally being viewed as justified and women as being held to higher moral standards. The researchers recommend that future studies employ more equal reporting practices for adultery and discriminate based on the gender of commentators.